1998
DOI: 10.1016/s0022-5223(98)70443-x
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive surgical management in localized pulmonary mycotic and nonmycotic infections for neutropenic patients with acute leukemia: Report of eighteen cases

Abstract: Aggressive surgical management radically improves the prognosis of invasive pulmonary aspergillosis, even if the surgical indications include some nonmycotic infections because of the difficulty in establishing the clinical diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
6

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 29 publications
1
26
0
6
Order By: Relevance
“…It should also be considered in cases of massive haemoptysis, pulmonary lesions close to the great blood vessels or pericardium, or residual localised pulmonary lesions in patients with continuing immunosuppression or those who are expected to have immunosuppressive therapy in the future. Several reports have shown the relative efficacy and safety of surgical intervention, in addition to antifungal therapy, in these situations [75,[157][158][159][160][161][162].…”
Section: Treatmentmentioning
confidence: 99%
“…It should also be considered in cases of massive haemoptysis, pulmonary lesions close to the great blood vessels or pericardium, or residual localised pulmonary lesions in patients with continuing immunosuppression or those who are expected to have immunosuppressive therapy in the future. Several reports have shown the relative efficacy and safety of surgical intervention, in addition to antifungal therapy, in these situations [75,[157][158][159][160][161][162].…”
Section: Treatmentmentioning
confidence: 99%
“…To obviate IPA relapse, some authors have suggested the resection of residual lesion(s) in addition to medical therapy. This was suggested in patients suffering from haematological malignancies [18,[172][173][174][175][176][177][178][179][180][181]. In this setting, surgery was proposed when the lesions were close to pulmonary vessels to avoid life-threatening haemorrhage in the neutrophils' recovery period [18], or in case of diagnostic procedure.…”
Section: Surgerymentioning
confidence: 99%
“…Although surgery could theoretically be considered in selected cases, both because it could be the only way to be fully curative and because minimal resection, such as wedge resection, might limit the functional defect [176,180,182], no recent study has been published to support this strategy.…”
Section: Surgerymentioning
confidence: 99%
“…However, about 20% of patients who underwent surgery did not have IPA. 4,5 IPA has to be considered if antibiotic resistant fever develops in neutropenic patients, with infiltrates on the chest X-ray. Typical thoracic computed tomography (CT) changes include the halo-sign, air crescent sign, or cavitary lesions.…”
mentioning
confidence: 99%
“…5 CT scan has a diagnostic sensitivity of 72-82% in patients with histologically proven IPA. 4,5 Bronchoscopy with bronchoalveolar lavage is an established method for the diagnosis of infectious pulmonary complications in neutropenic patients. 7 Respiratory tract cultures for IPA are regarded as highly specific, but rather low in sensitivity.…”
mentioning
confidence: 99%